Health Financing and Budgeting Practices Key findings from the Asia, Oceania, and Central, Eastern and South-eastern European regions - Ruiz, Ana Maria (OECD Publishing, 2019)
This article presents the findings of the OECD Survey of Senior Budget Officials on Budgeting Practices from a 2017 survey covering the Asia and Oceania, and Central, Eastern and South Eastern European regions. The survey is part of the ongoing engagement between health and budget officials in the OECD's regional networks and provides an comparable set of data to analyse and benchmark good practices in health budgeting. The results of the survey point to an increasing use of budgeting tools from developed countries and support continued engagement to improve budget activities and to meet future challenges of health systems